Toxicity effect of the acaricide fipronil in semi-engorged females of the tick Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae): Preliminary determination of the minimum lethal concentration and LC50 - de Oliveira, Patricia Rosa [UNESP]; Bechara, Gervasio Henrique [UNESP]; Denardi, Sandra Eloisi [UNESP]; Pizano, Marcos Aparecido [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Chemical acaricides, especially fipronil (active ingredient of Frontline (R)), are still the most effective method to control tick populations. In this study, the effectiveness of fipronil was assessed in semi-engorged females of the tick Rhipicephalus sanguineus. A protocol for an in vitro bioassay (AIT) was developed, and the LC50 (lethal concentration 50%) and 95% confidence interval were determined. Ticks were immersed in Petri dishes with different concentrations of fipronil or distilled water for 2 min, dried, and placed in an incubator for 7 days. Dead R. sanguineus females treated with the 14 concentrations of fipronil were counted daily. Mortality results were compared with the Probit analysis, and the LC50 and 95% confidence interval were calculated, g (95): LC50 = 9.647 (4.711 to 13.470). This study was aimed at developing a more appropriate and updated protocol for an in vitro bioassay (AIT - adult immersion test), and providing information on the toxic potential of fipronil (elimination of ectoparasites with lower concentrations) and sensitivity of ticks, especially R. sanguineus, a pest of great interest, due to its occurrence in urban environments. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Fipronil; Rhipicephalus sanguineus; Tick; LC50; Acaricide